Quelle place du sonore dans la production urbaine ? Éclairage par les postures et pratiques professionnelles dans le cadre du diagnostic sonore urbain - Théa Manola; Elise Geisler; Silvère Tribout; Jean-Dominique Polack (VertigO, 2018)
Based on a partial, often quantitative, negative and curative assessment of sound issues in urban projects, this article focuses on the way in which the various potential stakeholders of soundscape, consider the links between sound and urban space. For this purpose, this paper presents some results of a research project (Manola et al., 2017) involving several disciplinary fields (physical / acoustic, town planning, urban studies, geography, architecture) and funded by Agence de l'environnement et de la maîtrise de l'énergie (Ademe). The methodological approach of this research combines : bibliographic and documentary analyzes, field surveys and experiments (through workshops with professionals of the urban production and inhabitants, inspired by focus groups, and through a crossing seminar) on a single investigation / experimentation site : the garden-city of Stains (France). On this basis, the article aims to shed light on (1) the place and approaches of sound itself, in the practices and habits of the different professional groups ; (2) the tools mobilized by the different groups as well as their links to the "field" and to the "method" ; (3) the (power) relationships between these groups and the possibilities/conditions for taking sound issues into account in the urban fabric. Finally, we show the great diversity of approaches, tools and professional methods to invest the soundscape, and, nevertheless numerous continuing cognitive, organizational, strategic, financial and ideological resistances to a reinforced and transversal integration of the sound dimension in the production of the city.